2007
DOI: 10.1100/tsw.2007.294
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Fate, and Function of Epicardium-Derived Cells (EPDCs) in Normal and Abnormal Cardiac Development

Abstract: During heart development, cells of the primary and secondary heart field give rise to the myocardial component of the heart. The neural crest and epicardium provide the heart with a considerable amount of nonmyocardial cells that are indispensable for correct heart development. During the past 2 decades, the importance of epicardium-derived cells (EPDCs) in heart formation became increasingly clear. The epicardium is embryologically formed by the outgrowth of proepicardial cells over the naked heart tube. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
215
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 192 publications
(222 citation statements)
references
References 172 publications
(252 reference statements)
3
215
1
3
Order By: Relevance
“…Another option, is that abnormal epicardial-myocardial interaction plays a role in development of deficient myocardium as is seen in SP3 mutant mouse (Van Loo et al, 2007). We already described the deficient EPDC contribution in the podoplanin mutant (Lie-Venema et al, 2007;Mahtab et al, 2008). Therefore, both the hypoplasia of the atrial septum as well as the dorsal atrial wall observed in the current study, are related to the altered contribution of myocardial and epicardial cells from the PHF.…”
Section: Primary Atrial Septum and Dorsal Atrial Wallsupporting
confidence: 53%
See 1 more Smart Citation
“…Another option, is that abnormal epicardial-myocardial interaction plays a role in development of deficient myocardium as is seen in SP3 mutant mouse (Van Loo et al, 2007). We already described the deficient EPDC contribution in the podoplanin mutant (Lie-Venema et al, 2007;Mahtab et al, 2008). Therefore, both the hypoplasia of the atrial septum as well as the dorsal atrial wall observed in the current study, are related to the altered contribution of myocardial and epicardial cells from the PHF.…”
Section: Primary Atrial Septum and Dorsal Atrial Wallsupporting
confidence: 53%
“…Studying the mesenchymal population, podoplanin expression was observed in the proepicardial organ and epicardium Lie-Venema et al, 2007;Mahtab et al, 2008). In the cardiomyocyte population podoplanin staining was seen in major parts of the developing atrioventricular cardiac conduction system, in sinus venosus myocardium including the sinoatrial node, the venous valves, the dorsal mesocardium, the dorsal atrial wall and primary atrial septum.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardium added to the inflow tract (IFT) or venous pole is also derived from the second heart field, and has been referred to as posterior heart field (PHF; Mahtab et al, 2008). The outermost layer of the heart, the epicardium, develops initially as a cauliflower-like mesothelial primordium, the proepicardial organ (PEO), which is located near the sinus venosus (Viragh et al, 1993;Vrancken Peeters et al, 1999;Lie-Venema et al, 2007). In our view, the PEO is part of the PHFderived structures (Mahtab et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the more caudal position of the pulmonary and systemic veins in Id2 knockout embryos might represent a failure of correct looping of these hearts, resulting in either a ''primitive'' caudal position of these veins, or malpositioning of the inflow region of the heart dorsal to the ventricular segment, as was also observed in Tbx3 knockout embryos (Mesbah et al, 2008b). Thinning of the ventricular myocardium was described previously in mouse after mutation of podoplanin (Mahtab et al, 2008) and Pdgfr-a and in chick after epicardial ablation (Lie-Venema et al, 2007), and attributed in these models to disturbed epicardial contribution from the PHF.…”
Section: Arterial Pole Abnormalitiesmentioning
confidence: 65%